Expression and Clinical Significance of Various Checkpoint Molecules in Advanced Osteosarcoma: Possibilities for Novel Immunotherapy. Issue 3 (15th December 2022) - Xie, Lu; Chen, Chenglong; Liang, Xin; Xu, Jie; Sun, Xin; Sun, Kunkun; Yang, Rongli; Tang, Xiaodong; Guo, Wei
Abstract : Objectives: The fact that studies on anti‐programmed cell death 1 (PD‐1) or its relevant ligand 1 (PD‐L1) have yielded such few responses greatly decreases the confidence in immunotherapy with checkpoint inhibitors for advanced osteosarcoma. We intended to characterize the expression of various checkpoint molecules with immunohistochemistry in osteosarcoma specimens and analyzed the relationship of the expression of these checkpoint molecules with patients' clinical courses. Methods: This study was a retrospective non‐intervention study from August 1st 2017 to March 1st 2020. Immunohistochemistry for B7‐H3 (CD276, Cluster of Differentiation 276), CD47 (Cluster of Differentiation 47), PD‐L1 (programmed cell death ligand 1), TIM3 (mucin‐domain containing‐3), TGF‐β (TransformingGrowth Factor β), CXCR 4 (Chemokine Receptor 4), CD27 (Cluster of Differentiation 27), IDO1 (Indoleamine 2, 3‐dioxygenase 1), KIRs (Killer cell Immunoglobulin‐like Receptors), and SDF‐1 (Stromal cell‐Derived Factor‐1) was performed on 35 resected osteosarcoma specimens. Patients progressed upon first‐line chemotherapy with evaluable lesions were qualified for this study, and their specimens previously stored in the pathological department repository would be retrieved for analysis. Associations between the immunohischemistry markers and clinicopathological variables and survival were evaluated by the χ 2 displayed by cross‐table, Cox proportional hazards regression model, and Kaplan–Meier plots. Results: The positive rates of B7‐H3, CD47, PD‐L1, TIM3, and TGF‐β expression in this sample of 35 heavily treated osteosarcomas were 29% (10/35), 15% (5/35), 9% (3/35), 6% (2/35), and 6% (2/35), respectively, and diverse staining intensities were observed. Among these advanced patients, 15/35 (43%) had positive checkpoint expression, of which 33% (5/15) showed evidence of the co‐expression of more than one checkpoint molecule. We did not find any obvious correlation with clinicopathological characteristics and the positive expression of these molecules. Conclusions: The present study highlights that only a small subset of progressive osteosarcomas, which had been heavily‐treated, expressed tumor immune‐associated checkpoint molecules, of which B7‐H3 was the most positively expressed checkpoint and might be a promising target for further osteosarcoma investigation. Abstract : Clinical trials on anti‐programmed cell death 1 (PD‐1) have yielded few responses, which greatly decreases the confidence in anti‐PD‐1 therapy for advanced osteosarcoma. We examined 35 advanced osteosarcoma specimens, characterized the expression of various other immune‐checkpoint molecules with immunohistochemistry, and revealed that only a small subset of progressive osteosarcomas expressed tumor immune‐associated checkpoint molecules.